SS31 Ameliorates Podocyte Injury via Inhibiting OMA1-Mediated Hydrolysis of OPA1 in Diabetic Kidney Disease - Yang, Qianqian; Xie, Wenjia; Wang, Xiao; Luo, Jing; Zhou, Yang; Cao, Hongdi; Sun, Qi; Jiang, Lei; Yang, Junwei (Frontiers in Pharmacology, 2022)
Diabetic kidney disease (DKD) is currently one of the leading causes of end-stage renal disease (ESRD). Mitochondrial dysfunction in podocyte is involve in DKD development. However, whether early mitochondrial stabilization delays or reverses DKD progression has not been elucidated. SS31 is a novel tetrapeptide compound that targets the inner mitochondrial membrane and protects mitochondria by reducing ROS and inhibiting cardiolipin oxidation. Our study discovered that SS31 might have a long-term podocyte protection in DKD. In this study, we examined the glomerular pathological damage and proteinuria at different stages of diabetes. Results revealed that podocyte mitochondrial injury appeared at the early stage of DKD. Early treatment with SS31 could protect podocyte and alleviate the development of DKD via inhibiting OMA1-mediated hydrolysis of OPA1. Those data indicate that SS31 might be a promising agent in delaying the development of DKD and OMA1-mediated hydrolysis of OPA1 in mitochondria, and SS31 is a novel therapeutic target for the treatment of DKD.